2012
DOI: 10.1073/pnas.1220230110
|View full text |Cite
|
Sign up to set email alerts
|

Maternal exposure to bisphenol A and genistein has minimal effect onAvy/aoffspring coat color but favors birth of agouti over nonagouti mice

Abstract: Reports that maternal diet influences coat color in mouse offspring carrying the agouti A vy allele have received considerable attention because the range, from pseudoagouti (brown) to yellow, predicts adult health outcomes, especially disposition toward obesity and diabetes, in yellower mice. Bisphenol A (BPA), an endocrine-disrupting compound with estrogenic properties, fed to a/a dams harboring A vy /a conceptuses has been reported to induce a significant shift toward yellower mice, whereas consumption of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 81 publications
1
40
0
1
Order By: Relevance
“…Numerous studies have demonstrated that ROS scavengers such as n-acetylcysteine and tempol prevent epigenetic DNA methylation changes induced by oxidative stress (149)(150)(151). Similarly, oxidative stress mediated by intrauterine hypoxia was shown to be protected by administering DNMT inhibitors (137) or methyl donors such as genistein (152,153). Taken together, these studies demonstrate that exogenous application of antioxidant supplements protects the biological system by preventing aberrant epigenetic transformations.…”
Section: Discussionmentioning
confidence: 73%
“…Numerous studies have demonstrated that ROS scavengers such as n-acetylcysteine and tempol prevent epigenetic DNA methylation changes induced by oxidative stress (149)(150)(151). Similarly, oxidative stress mediated by intrauterine hypoxia was shown to be protected by administering DNMT inhibitors (137) or methyl donors such as genistein (152,153). Taken together, these studies demonstrate that exogenous application of antioxidant supplements protects the biological system by preventing aberrant epigenetic transformations.…”
Section: Discussionmentioning
confidence: 73%
“…The IAP transposable element that alters the coat color phenotype in these animals appears to be unusually susceptible to influences that alter the epigenome, such as dietary influences in mice exposed to endocrine active substances (Dolinoy et al, 2007), generating a readout in terms of coat color, which is easily recognizable, and allowing direct analysis of the IAP element in terms of its cytosine methylation as a more quantitative readout (Waterland and Jirtle, 2003). However, as described later in Section 7.3, the evaluation of these viable yellow mice as a model suitable for toxicology studies has not proven to be encouraging and in contrast to the studies by Dolinoy et al (2007), recently Rosenfeld et al (2013) showed bisphenol A (BPA) exposure in Agouti mice did not alter coat color distribution.…”
Section: Issues To Address When Considering An Epigenomics Studymentioning
confidence: 99%
“…The viable yellow (A vy ) mouse model was described earlier (Section 6), allowing screening for effects of exposures during pregnancy by the use of coat color or cytosine methylation analysis of the IAP element (Waterland and Jirtle, 2003). However, in contrast to these studies, recently Rosenfeld et al (2013) showed BPA exposure in Agouti mice did not alter coat color distribution, but there was a suggestion that Agouti A vy conceptuses may possess a "thrifty" genotype and be at a competitive advantage in certain uterine environments that can predispose the offspring to metabolic syndrome when food is plentiful. This may therefore not be such a useful mouse resource.…”
Section: Potential New Test Systemsmentioning
confidence: 99%
“…Epigenetic modifications include DNA methylation, histone modifications, and the expression of non-coding RNAs (reviewed in Yamada and Chong, 2016). Agouti viable yellow (A vy ) is a metastable epiallele that has been extensively studied as an epigenetic biosensor in various models of prenatal environmental exposures, including those of ethanol, soy protein isolate, bisphenol A, genistein, methyl supplementation, and even in vitro culturing of zygotes (Badger et al, 2008;Rosenfeld et al, 2013;Anderson et al, 2012;Dolinoy et al, 2007Dolinoy et al, , 2006Kaminen-Ahola et al, 2010b;Cooney et al, 2002;Morgan et al, 2008). The Agouti gene contributes to coat colour in mice (Morgan et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The variable expression of A vy is linked to DNA methylation within an Intracisternal-A Particle (IAP) retrotransposon insertion ∼100 kb upstream of the hair-cycle specific promoters. It is this distribution of coat colours, which are used as a proxy marker for methylation at this locus, that has been reported to be altered following various prenatal exposures (Badger et al, 2008;Rosenfeld et al, 2013;Anderson et al, 2012;Dolinoy et al, 2007Dolinoy et al, , 2006Kaminen-Ahola et al, 2010b;Blewitt et al, 2006;Cooney et al, 2002;Morgan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%